Increased kallistatin levels in patients with obesity and prediabetes compared to normal glucose tolerance. (3rd April 2017) - Gateva, Antoaneta; Assyov, Yavor; Velikova, Tsvetelina; Kamenov, Zdravko
ABSTRACT: Purpose : Kallistatin is a member of serine protease inhibitors (SERPIN) family, which has various functions such as regulation of cardiovascular function and blood vessels development. Its levels are elevated in patients with type 1 and type 2 diabetes with chronic diabetic complications. The aim of the present study was to compare serum kallistatin levels between obese subjects with prediabetes and with normal glucose tolerance.Methods : In this study we included 80 subjects at mean age of 50.4 ± 10.6 years, divided into two age and BMI-matched groups – group 1 with obesity without glycemic disturbances ( n = 41) and group 2 with obesity and prediabetes ( n = 39). Oral glucose tolerance test with measurement of immunoreactive insulin was performed in all participants and levels of kallistatin were measured using ELISA method.Results : We found significantly higher levels of kallistatin in patients with prediabetes compared to controls (data are presented as median (min; max) because data were not normally distributed) (6.3 (4.4; 9.0) vs. 5.6 (3.1; 8.7) ng/ml; p = 0.022) and in patients with metabolic syndrome compared to those without (6.0 (4.9; 9.0) vs. 5.5 (3.1; 7.7); p = 0.006), but the levels were similar in patients with and without insulin resistance.Conclusions : The levels of kallistatin are higher in individuals with prediabetes, but are similar in subjects with and without insulin resistance, which indicates that the main factor for its increased levels may be hyperglycemia and not insulin sensitivity state.